Influence of Soilless Growing Media Comprising Industrial By-products on Growth of Foliage Plants Epipremnum aureum and Dracaena sp. - Shree, K. G. Shilpa; Safeena, S. A.; Kumar, P. Naveen; Prasad, K. V.; Girish, K. S. (International Journal of Bio-resource and Stress Management, 2024)
Experiments were conducted during August, 2020 to April, 2021 at the ICAR-Directorate of Floricultural Research, Pune, Maharashtra, India to assess the suitability of industrial by-products fly ash and press mud as growing media component for foliage plants Epipremnum aureum and Dracaena sp. Different growing media compositions comprising of fly ash, press mud, cocopeat and vermicompost were evaluated in varying proportions. Foliage plants growth was monitored for nine months duration. Initial pH and electrical conductivity of growing media compositions were determined and leaf samples were analyzed for macro and micronutrients content at the end of the experiment. pH of growing media compositions ranged from near neutral to slightly alkaline pH and electrical conductivity of all media compositions was less than 1.0 dS m-1. Results indicated that growing media composition Fly ash+Vermicompost+Cocopeat (20:30:50) was the most suited growing media to grow Epipremnum aureum under 50% shade condition. Media compositions Cocopeat+Vermiculite+Perlite (33.3:33.3:33.3) and Fly ash+Vermicompost+Cocopeat (20:30:50) were observed to be more suited for growth of Dracaena sp. under 50% shade condition. Maximum plant height, number of leaves, leaf size and petiole length were recorded in Epipremnum aureum and Dracaena sp. plants grown in above media compositions respectively. Results inferred that fly ash along with vermicompost and cocopeat can be used as a growing media component for production of foliage plants Epipremnum aureum and Dracaena sp.